Using multi-criteria analysis to identify suitable light rail transit route - Muhamad Ludin, Ahmad Nazri; Mohd. Latip, Siti Noor Haslinda (2006)
Public transportation planning and development are undergoing continuous changes often prompted by both external factors and policy-directed responses. The role of public transit, particularly rail transit, becomes increasingly importance with the changing demographic and economic pattern. The trend of returning to urban living for e.g. has significantly increased the demand for efficient public transportation in urban centres. However, the design and development of Light Rail Transit (LRT) route seldom takes into consideration land use changes and demand. This paper investigates how non-spatial and spatial data can be integrated within a multi criteria decision framework to formulate and evaluate land use development corridor to determine suitable route for LRT. A raster base multi-criteria analysis model was developed base on a set and specific objectives, criteria, indicator and data requirement. The set criteria and indicator proposed are in line with the objectives to improve public transportation as stipulated in the Kuala Lumpur Structure Plan. A case study approach is undertaken within a selected LRT railroad in Kuala Lumpur, Malaysia. The model, integrating GIS and external software, shows that suitable LRT alignment can be identified that take into account social, institutional and environmental objectives. The approach will assist in the planning and development of LRT network, and thus maximizing usage of rail-based public transport to serve the community.